A preliminary study on the effects of a transgenic corn event on the non-target pest Dalbulus maidis (Hemiptera: Cicadellidae) - Virla, Eduardo Gabriel (2010)
The inclusion of the cry gene in corn may produce direct effects on non-target pests. Our research was focused on the relationship between Bt corn germplasm, expressing the cry1F protein to control the fall armyworm [Spodoptera frugiperda (Noctuidae)], and a non-target pest, the corn leafhopper [Dalbulus maidis (Cicadellidae)]. The aim of this contribution was to elucidate if Bt corn plants have influence on the oviposition preference of the leafhopper and to evaluate the effect of the transgenic plant on the hatching rate of egg. Female corn leafhoppers were released in cages each containing two potted plants in the V2 stage: a Bt germplasm and the corresponding isogenic hybrid. Laid eggs were counted and the number of hatched nymphs recorded. D. maidis females oviposited and laid more eggs in Bt plants. The egg hatching rate was negatively affected by the Bt germplasm. In addition, a field study was conducted in order to determine the abundance of D. maidis adults in Bt corn and the corresponding non-Bt isoline. Two corn plots sown with the same germplasms as used in the laboratory bioassays were sampled weekly. In the field, the population of the corn leafhopper was higher in the Bt corn plot than in the non-Bt isoline. Possible hypotheses for the differences in abundance of the vector in the field are: a) that pleiotropic effects of Bt corn could attract adults; b) the existence of a possible direct competition between the corn leafhopper and the target pest in order to utilize the whorls of corn plants as refuge and feeding sites, so the high populations of the vector could be due to the large supply of healthy whorls in the transgenic plot; and/or c) a differential attack of natural enemies occurring in non-Bt plots.